Clinical impact of strontium and zinc on bone and cartilage regeneration processes, an approach from biology to the clinic. Literature review - Urbano del Valle, Samuel (2021)
Many systemic disorders such as arthritis or osteoporosis are pathologies responsible of temporomandibular joint chronic dysfunctions, thus creating a long-term problem that affects life´s quality of those who suffer from them. Currently there is no curative treatment for these pathologies, although there is a palliative treatment, which in many cases have side effects over time or a limitation in their effectiveness and efficacy, so it is necessary to look for alternatives with the implementation of regenerative therapies for treatment of those diseases that affect musculoskeletal system. In many studies the fundamental role of zinc and strontium in genesis of both cartilaginous and bone tissue is discussed, as well as the relevance of incorporating them with various biomaterials in regeneration procedures, however, this issue is not clear yet and requires more attention from the clinician. The objective of this article is to determine function of zinc and strontium in regeneration processes of bone and cartilage from a molecular and cellular perspective applied to clinical practice, in order to obtain new alternatives in the treatment of various pathologies and musculoskeletal alterations that improve the oral health conditions of patients. In addition, this review brings us closer to understanding the mechanisms of action of different molecules that when incorporated into biomaterials compatible with hard and soft tissue improve the biological conditions for the regeneration.